Perancangan Sepeda Listrik Semoli Untuk Beban 80 Kg - Bayu Aji Girawan; Nur Akhlis Sarihidaya Laksana; Dian Prabowo (Accurate: Journal of Mechanical Engineering and Science, 2022)
Electric bike is environmentally friendly vehicle because it doesn’t cause air pollution and it can uses electric from renewable energy sources to charge battery. Here is a lot of studies about electric bike in Indonesa, but only a few topic about electric bike for uphill climbing. In this study, electric bike will be designed for a load of 80 kgs to overcomes the uphill road at 21° of elevation. The design process contains activity such as calculation and selection of electric motor, drafting and manfacturing the frame, and riding test on flat road and uphill road at 21° of elevation. The results of design, electric bike uses 2000 watt BLDC motor, 48V 20Ah of battery, 13 teeth at front sprocket and 48 teeth of rear sprocket. From the riding test results, the bike’s maximum speed is 35 km/h reached on 5 seconds on flat road. While on uphill road with elevation of 21°, the bike’s maximum speed is 10 km/h reached on 10 seconds. The conclusion from this study that the electric bike are able to meet the needs to overcome uphill road.